Evaluation of Redox Profiles of the Serum and Aqueous Humor in Patients with Primary Open-Angle Glaucoma and Exfoliation Glaucoma - Yuji Takayanagi; Yasuyuki Takai; Sachiko Kaidzu; Masaki Tanito (MDPI AG, 2020)
Oxidative stress is thought to play a significant role in the development of glaucoma. However, the association between systemic and local oxidative stresses in different types of glaucoma has not been assessed fully. The current study compared the redox status in the aqueous humor (AH) and blood samples among eyes with primary open-angle glaucoma (POAG), exfoliation glaucoma (EXG), and non-glaucomatous controls to evaluate the relationship among systemic redox status, intraocular oxidative stress, and clinical backgrounds. AH and blood samples were obtained from 45 eyes of 45 Japanese subjects (15 POAG, 15 EXG, and 15 control eyes). The serum levels of lipid peroxides, ferric-reducing activity, and thiol antioxidant activity were measured by diacron reactive oxygen metabolites (dROM), biologic antioxidant potential (BAP), and sulfhydryl (SH) tests, respectively, using a free radical analyzer. The activities of cytosolic and mitochondrial forms of the superoxide dismutase (SOD) isoforms, i.e., SOD1 and SOD2, respectively, in AH and serum were measured using a multiplex bead immunoassay. In AH, SOD1 in subjects with EXG and SOD2 in those with POAG and EXG were significantly higher than in control eyes. In serum, compared to control subjects, BAP in subjects with POAG and EXG was significantly lower; SOD1 in those with EXG and SOD2 in those with POAG and EXG were significantly higher. dROM and SH did not differ significantly among the groups. The BAP values were correlated negatively with the SOD1 concentrations in AH and serum, SOD2 in the AH, intraocular pressure, and number of antiglaucoma medications. In conclusion, lower systemic antioxidant capacity accompanies up-regulation of higher local antioxidant enzymes, suggesting increased oxidative stress in eyes with OAG, especially in EXG. Determination of the systemic BAP values may help predict the redox status in AH.